2018
DOI: 10.20517/cdr.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid metabolism and drug resistance in ovarian cancer

Abstract: Despite progress in understanding molecular aberrations that contribute to the development and progression of ovarian cancer, virtually all patients succumb to drug resistant disease at relapse. Emerging data implicate bioactive sphingolipids and regulation of sphingolipid metabolism as components of response to chemotherapy or development of resistance. Increases in cytosolic ceramide induce apoptosis in response to therapy with multiple classes of chemotherapeutic agents. Aberrations in sphingolipid metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 138 publications
1
18
0
Order By: Relevance
“…In fact, a resensitization to paclitaxel of taxane-resistant SKOV3.TR ovarian cancer cells have been shown with the combination of paclitaxel with C6-ceramide-encapsulated in poly(ethylene oxide)-modified poly(epsilon-caprolactone) (PEO-PCL) nanoparticles (235). Kelly M. and colleagues demonstrated that the combined treatment of tamoxifen with the Sphingosine kinase 1 (SK1) inhibitor FTY720 blocks proliferation of both ERα-positive and ERα-negative drug-resistant cell lines and an ERα-positive PDX model of ovarian tumor (240). The multiple mechanisms of action of tamoxifen and its relatively high therapeutic index provide a strong rationale for combining tamoxifen with FTY720, as a strategy for treating ovarian tumors and circumventing drug resistance (226,(241)(242)(243).…”
Section: Targeting Lipid Metabolismmentioning
confidence: 99%
“…In fact, a resensitization to paclitaxel of taxane-resistant SKOV3.TR ovarian cancer cells have been shown with the combination of paclitaxel with C6-ceramide-encapsulated in poly(ethylene oxide)-modified poly(epsilon-caprolactone) (PEO-PCL) nanoparticles (235). Kelly M. and colleagues demonstrated that the combined treatment of tamoxifen with the Sphingosine kinase 1 (SK1) inhibitor FTY720 blocks proliferation of both ERα-positive and ERα-negative drug-resistant cell lines and an ERα-positive PDX model of ovarian tumor (240). The multiple mechanisms of action of tamoxifen and its relatively high therapeutic index provide a strong rationale for combining tamoxifen with FTY720, as a strategy for treating ovarian tumors and circumventing drug resistance (226,(241)(242)(243).…”
Section: Targeting Lipid Metabolismmentioning
confidence: 99%
“…Downregulation of SphK2 with siRNA inhibited proliferation of glioblastoma cells more potently than that observed for SphK1 knockdown (van Brocklyn et al, ), suggesting that SphK2 is a more viable candidate for chemotherapeutic targeting. Based on previous studies, SphK2 has the differential ability to be involved in either extrinsic or intrinsic pathway of apoptosis, depending on the type of cell line studied, presence or absence of serum, growth factors and glucose, the type of chemotherapeutic/agent used, as well as other stressors such as hypoxia (Kreitzburg et al, ; Mizutani et al, ; Okada et al, ).…”
Section: Development Of Resistance By Sphk2 Via Aberrant Regulation Omentioning
confidence: 99%
“…SM consists of a phosphocholine head group and ceramide contained sphingosine and fatty acids and its subcellular location is correlated with cholesterol [ 91 ]. It is important to acquire a resistance to anticancer agents since ovarian cancer cells provoke an aberrant SM mechanism that involves the promotion of the catabolism of ceramide, and the production and accumulation of ceramide [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%